ID 275 – OCT and VEP in Multiple Sclerosis: Sensitivity and predictive value. Issue 3 (March 2016) - Di Maggio, G.; Santangelo, R.; Guerrieri, S.; Ferrari, L.; Vitali, F.; Medaglini, S.; Rodegher, M.; Colombo, B.; Moiola, L.; Del Carro, U.; Martinelli, V.; Comi, G.; et al.
Abstract : To evaluate the role of optical coherence tomography (OCT) and visual evoked potentials (VEPs) in patients with multiple sclerosis (MS). Study of 121 consecutive subjects with MS. Of 242 eyes, 166 had no previous history of optic neuritis (ON), 22 had a single recent ON episode (3 months before). All patients underwent assessment of EDSS, OCT retinal nerve fiber layer (RNFL) thickness and VEP. 77 subjects underwent to a second EDSS (EDSS2) evaluation after a mean time of 1, 94 years. In eyes with recent ON, the sensitivity of OCT was 38.9% with a higher sensitivity of VEP (77.3%; McNemar p < 0.02). In eyes with chronic ON, no significant difference was found between OCT (68.5%) and VEP (81.5%) sensitivity. In asymptomatic eyes, VEPs had a higher sensitivity (31.7%) vs. OCT (19.9%; p = 0.005); VEP/OCT combined detected abnormalities in 39.2%. In follow up evaluation, OCT alterations were associated with development of disability after 2 years ( p = 0.013). VEP alterations did not predicted future disability development.The present findings confirm a higher sensitivity of VEPs in the subacute phases of optic neuritis and in asymptomatic eyes. In eyes without previous optic neuritis, early asymptomatic OCT abnormalities are associated with short-term worsening of disability.